NILAI PROTEIN, B-KAROTEN DAN SENSORIS BISKUIT BAYI DARI TEPUNG UBI JALAR KUNING, TEPUNG KECAMBAH KACANG HIJAU DAN TEPUNG MILLET TERFERMENTASI - IDP Kartika Pratiwi; NM Indri Hapsari Arihantana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2019)
Innovation baby biscuits from composite flour using local raw material such as yellow sweet potatoes,green bean and millet is important to diversification. This research aims to determine the proteincontent, ?-carotene and sensory properties of Baby Biscuits from 9 types composite flour formulas. Theexperimental design was a complete randomized design with a 9 composite flour formulas and repeated2 times, the proportion of yellow sweet potatoes flour : green bean sprouts flour : fermented millet flournamely 60:25:15; 55:30:15; 50:35:15; 55:25:20; 50:30:20; 45:35:20; 50:25:25; 45:30:25; 40:35:25.The results of the analysis stated that the comparison of the composition of composite flour has asignificant effect on the value of protein, ?-karoten, sensory test of taste and crispness of baby biscuits.The best formulation was obtained in baby biscuits made with the propotion of yellow sweet potatoesflour : green bean sprouts flour : fermented millet flour of 50:35:15. Those baby biscuits contained8.51% protein, 398.18 g/100g ?-carotene, taste is like (5.93) and crispness level is crispy (4.20).